Molecular interactions of nitrogen-containing bisphosphonates within farnesyl diphosphate synthase - Ebetino, F; Roze, C; McKenna, C; Barnett, B; Dunford, J; Russell, R; Mieling, G; Rogers, M (2005)
Bisphosphonates, known for their effectiveness in the treatment of osteoporosis, inhibit bone resorption via mechanisms that involve binding to bone mineral and cellular effects on osteoclasts. The major molecular target of nitrogen-containing bisphosphonates (N-BPs) in osteoclasts is farnesyl diphosphate synthase (FPPS). N-BPs likely inhibit this enzyme by mimicking one or more of the natural isoprenoid lipid substrates (GPP/DMAPP and IPP) but the mode of inhibition is not established. The active site of FPPS comprises a subsite for each substrate. Kinetic studies with recombinant human FPPS indicate that both potent (risedronate) and weak (NE-58051) enzyme inhibitors compete with GPP for binding to FPPS, however, binding to this site does not completely explain the difference in potency of the two inhibitors, suggesting that a second binding site may also be a target of bisphosphonate inhibition. Using the docking software suite Autodock, we explored a dual inhibitor binding mode for recombinant human FPPS. Experimental support for dual binding is suggested by Dixon plots for the inhibitors. N-BPs may inhibit by binding to both the GPP and a second site with differences in potency at least partly arising from inhibition at the second site. © 2005 Published by Elsevier B.V.